Minor components and wheat quality: Perspectives on climate changes. (July 2020) - Marion, Didier; Saulnier, Luc
Abstract: Minor compounds of cereal grains such as lipids and cell wall polysaccharides play an important role in their milling properties, their transformation into baked cereal products and their nutritional properties. These effects are mainly due to their interactive properties, such as their ability to absorb large amounts of water for polysaccharides or to interact with starch polymers and proteins for lipids. Environmental stress induced by climate change and regulations for environmentally friendly agriculture can interfere with the biosynthesis of these minor grain compounds as well as the main compounds starch and protein. Indeed, the metabolic networks of all components of the endosperm of grains are closely associated. Therefore, in the context of climate change and agricultural sustainability, lipids and cell wall polysaccharides may be affected. Contrasting with a plethora of studies reporting the impact of environment and fertilizer on cereal proteins, there is a real lack of information on this particular topic for these minor compounds. However, our knowledge of the physico-chemical properties and biosynthesis of these minor compounds allows us to assess the likely strong impact of environmental and agronomic constraints on the relationships between cell wall polysaccharides, lipids and cereal quality. Highlights: Cereal grains lipids and cell wall polysaccharides impact cereal products quality. Lipids and cell walls are heterogeneously distributed in cereal grains. Lipids & cell wall polymers content and proportion are affected by climate change.